SYNTHESIS OF ANALOG L-α-METIL-DOPA FROM EUGENOL - Hanoch J Sohilait; Hardjono Sastrohamidjojo; Sabirin Matsjeh; J Stuart Grossert (Universitas Gadjah Mada, 2005)
Synthesis of analog L-α-metil-Dopa from eugenol has been achieved through conversion of allyl group to ketone, followed by reaction with NH3 and KCN and by hydrolisis. The addition reaction of methyleugenol with formic acid yield methyleugenyl formate (60,69%). The hydrolis of methyileugenylformate with KOH in aqaueous-ethanolic solution produced methyleugenyl alcohol (73,68%). The oxidation of methyleugenyl alcohol with PCC yield methyleugenyl ketone (67,71%). The reaction of methyleugenyl ketone with NH3 and KCN yield D,L-α-amino-α-(3,4-dimetoxybenzyl) propionitril (84,14%). The hydrolisis of D,L-α-amino-α-(3,4-dimetoxybenzyl) propionitril with concentrated hydrochloric acid gave Analog L-α-metil-Dopa as a main target (91,98%). The structure elucidation of these products were analyzed by FTIR, 1H-NMR, 13C-NMR and MS